Colour terms in five linguistic images of the world : the semantic perspective - Golda, Paweł; Jedziniak, Agnieszka; Mężyk, Judyta; Ryszka, Joanna; Uchman, Teresa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Social and cultural factors shape the linguistic perception of colour. At the same time, colour terms co-create the linguistic image of the world, which allows us to interpret reality and profile our statements and beliefs. This paper presents six basic colour terms: white, black, red, green, yellow, and blue (both as adjectives and as nouns) in the five different linguistic images of the world of the following languages: English, French, Italian, Polish, and Japanese. The methodological framework is based on cultural linguistics theory and the basis of semantics. The study explores denotative and connotative meanings of colour terms with their collocations. The data gathered from monolingual, bilingual, collocation, and phraseological dictionaries is analysed from the lexical-semantic point of view. The paper discusses semantic differences between contrasting cultures, especially in the blue-green and red lexis. Simultaneously, the findings point to transcultural and global aspects of colour meanings. Both the contexts of cultural diversity and of geographic location are emphasised in the colour semantics. Colours as linguistic signs can specify and categorise reality in terms of feelings, mental attitudes, or sensual reactions. The examined words also refer to location, nature, and the human body. The study shows that colour terms are multifunctional units in the linguistic image of the world, both in terms of the analysed languages separately and as an illustration of the cultural community of different ethnic languages.